Tipi di costrutti coordinati e subordinati nel testo descrittivo: il croato e l'italiano a confronto - Deželjin, Vesna (2009)
The paper shows that usage of some connection structures in descriptive texts in Croatian and Italian does not always depend on the language acquisition level.